“They can achieve their aims without native skills in the field of work or studies”: Hungarian students’ views on English as a lingua franca - Kontra, Edit H.; Csizér, Kata (Studies in Second Language Learning and Teaching, 2011)
Despite the fact that there is a growing body of research on the characteristics and use of English as a lingua franca (ELF) in Europe, there are relatively few studies aimed at investigating the ways in which language learners voice their opinions about ELF and how they see ELF impacting their own learning. Therefore, the aim of the present study is to find out what English language majors (and ELF users) think about ELF. In order to get an insiders’ perspective on the issue, 250 one-paragraph argumentative essays on the necessity of learning to speak like a native or using ELF were analyzed for their content. The main results show the investigated sample’s predictable though not unanimous preference for prestigious native varieties. More pertinent to this article is that in spite of this preference the students demonstrate a definite awareness of ELF expressed in a large number of statements acknowledging the worldwide importance of knowing English and that today English is used by far more non-native than native speakers of the language. Though not all our research participants favor the use of ELF, many of them see it as a necessity.